2014
DOI: 10.7863/ultra.33.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Systolic Deformation and Dyssynchrony Indices and the Grade of Left Ventricular Hypertrophy in Hypertensive Patients With a Preserved Systolic Ejection Fraction Undergoing Coronary Angiography, Based on Tissue Doppler Imaging

Abstract: Among tissue Doppler and deformation indices, overall peak systolic strain was the strongest correlate of the LV hypertrophy grade. Therefore, in hypertensive patients with normal cardiac systolic function, a reduction in overall strain in the 6 basal LV segments may be a good indicator of progression of the LV hypertrophy grade and systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This decreased LV synchrony could be attributed to increased sodium retention and high blood pressure. Indeed, some studies have shown that hypertension causes LV remodeling and alters myocardial electrophysiological properties, such as increased cardiomyocyte autorhythmicity and potential instability, myocardial electrophysiological conduction block, and myocardial excitation-contraction coupling dysregulation, all of which may lead to impaired LV systolic synchrony [37,38]. Due to excessive volume overload, elevated peripheral blood pressure, and lack of ATP, LV contraction time is extended as a compensatory mechanism to insure adequate cardiac output [39].…”
Section: Discussionmentioning
confidence: 99%
“…This decreased LV synchrony could be attributed to increased sodium retention and high blood pressure. Indeed, some studies have shown that hypertension causes LV remodeling and alters myocardial electrophysiological properties, such as increased cardiomyocyte autorhythmicity and potential instability, myocardial electrophysiological conduction block, and myocardial excitation-contraction coupling dysregulation, all of which may lead to impaired LV systolic synchrony [37,38]. Due to excessive volume overload, elevated peripheral blood pressure, and lack of ATP, LV contraction time is extended as a compensatory mechanism to insure adequate cardiac output [39].…”
Section: Discussionmentioning
confidence: 99%
“…This decreased LV synchrony could be attributed to increased sodium retention and high blood pressure. Indeed, some studies have shown that hypertension causes LV remodeling and alters myocardial electrophysiological properties, such as increased cardiomyocyte autorhythmicity and potential instability, myocardial electrophysiological conduction block, and myocardial excitation-contraction coupling dysregulation, all of which may lead to impaired LV systolic synchrony (37)(38). Due to excessive volume overload, elevated peripheral blood pressure, and lack of ATP, LV contraction time is extended as a compensatory mechanism to insure adequate cardiac output (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accurate assessment of cardiac function should be combined with the coordination and synchronization of myocardium mechanical movement. The newly developed PSD index combines the myocardial deformation and whether the deformation of 17 myocardial segments is uniform in the LV 10,12 . The above two factors were combined to evaluate LV systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging study of peak strain dispersion (PSD) identifies whether the peak time of long axis strain of LV myocardium is consistent, which can directly reflect the effective work of the heart and make up for the deficiency of GLS in evaluating LV systolic function [10][11][12] . PSD is used to evaluate the early systolic dysfunction of LV by combining the coordination and synchronization of cardiac mechanical movement, and this index has been applied to assess early LV systolic dysfunction in some diseases, such as mitral valve prolapse 13 , aortic stenosis 14…”
Section: Value Of Peak Strain Dispersion In Discovering Left Ventricumentioning
confidence: 99%